Awareness and compliance of dental students and interns toward infection control at Riyadh Elm University - Binalrimal, Sultan; AlDrees, Abdulmajed; AlWehaibi, Mohammed; AlAsmary, Mohammed; AlShammery, Abdulaziz; AlHaidri, Essam; AlQabbaa, Lama (German Medical Science GMS Publishing House, 2019)
Aim: Dental students have increasing patient contact during their education and clinical years, putting them at high risk of cross-infection; therefore, the purpose of this study was to determine the level of infection control practices among dental students and interns at Riyadh Elm University, Riyadh, Saudi Arabia. Methods: Total of 400 questionnaires were distributed among interns and clinical students at Riyadh Elm University. The questionnaire comprised 32 items assessing infection control practices, and the data were tabulated and analyzed by SPSS to produce descriptive statistics.Results: Three hundred nine questionnaires were answered (response rate 77%).The implementation of different infection control measures was good to excellent, except for hepatitis B vaccination and wearing eye protection: only 76% of males and 83% of females were vaccinated against HBV, and only 30% of males and 26% of females always wore protective glasses. Conclusion: Compared to previous studies, an increased awareness regarding infection control practices among dental students and interns was noticeable. However, greater emphasis on the importance of infection control, especially compliance with HBV vaccination and wearing protective eyewear, is necessary.